Indicadores de competitividad para la internacionalización del departamento del Valle del Cauca entre el 2017 - 2022 Paula Andrea Avirama Castrillon 20702018845 Universidad Antonio Nariño Programa Comercio internacional Facultad de Ciencias Económicas y Administrativas Cali, Colombia 2023 (2023)
This document identifies a set of competitiveness indicators and their relationship with internationalization in the department of Valle del Cauca in the period 2017-2022. To achieve this purpose, the competitiveness of the Department is evaluated considering 12 pillars grouped in 3 sub-indices: basic elements, efficiency and innovation enhancers, and sophistication. These sub-indices measure competitiveness indicators related to: sophistication, diversification, and market size calculated by the Private Competitiveness Council. For this purpose, a descriptive correlational methodology is used, starting with data collection, selection of indicators, bibliographic review and analysis of quantitative and qualitative data provided by the Private Competitiveness Council, the National Competitiveness Commission, the National Tax and Customs Directorate, among other sources of information related to exports from the department that are related to internationalization in this work